1998
DOI: 10.1177/107385849800400312
|View full text |Cite
|
Sign up to set email alerts
|

Review : Apoptosis and Spinal Cord Injury

Abstract: Apoptosis is the morphological counterpart of active, genetically programmed cell death and is important in development, immune function, and carcinogenesis. Recent data suggest that apoptosis may be important in neurodegenerative disorders, ischemic brain injury, and neurotrauma as well. Here we review very recent data from our laboratory and others that show that at least some of the pronounced secondary injury that follows spinal cord injury (SCI) may be caused by apoptosis and associated intracellular deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 61 publications
1
12
0
2
Order By: Relevance
“…We have demonstrated previously that short term infusion of vMIPII also results in neuronal survival. Because apoptotic cell death after acute spinal cord injury has been postulated to play a pivotal role in the secondary injury cascade (Beattie et al, 1998; Lou et al, 1998), we determined whether the survival of neurons in antagonist infused spinal cord was a result of reduced apoptosis. Because bcl‐2 has been suggested to be one of the proteins preventing apoptosis in a variety of cells, vehicle and vMIPII infused spinal cord sections at 3 and 6 weeks post‐injury were stained with anti bcl‐2 antibody.…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated previously that short term infusion of vMIPII also results in neuronal survival. Because apoptotic cell death after acute spinal cord injury has been postulated to play a pivotal role in the secondary injury cascade (Beattie et al, 1998; Lou et al, 1998), we determined whether the survival of neurons in antagonist infused spinal cord was a result of reduced apoptosis. Because bcl‐2 has been suggested to be one of the proteins preventing apoptosis in a variety of cells, vehicle and vMIPII infused spinal cord sections at 3 and 6 weeks post‐injury were stained with anti bcl‐2 antibody.…”
Section: Resultsmentioning
confidence: 99%
“…Injury to the white matter is characterized by the widespread distribution of injured axons, which, in the acute post-traumatic stage, appear as swollen fibers containing accumulated cytoskeletal proteins (39). Over time, these swollen axons eventually undergo complete axotomy reminiscent of Wallerian degeneration (86), a process that is associated with death of oligodendrocytes (5). Traumatic oligodendrocyte death may also be induced by the reactive microglia and astrocytes present in the white matter (23, 39, 102).…”
Section: Regional Cell Death Patterns Following Tbimentioning
confidence: 99%
“…Neurons that survive axotomy can also contribute to recovery, even in the absence of regeneration, if they remain part of spinal circuitry rostral to the injury. The recognition that retrograde neuron death has many of the features of apoptosis (Crowe et al, 1997; reviewed by Beattie et al, 1998) has suggested several different therapeutic strategies for increasing neuron survival and recovery. These strategies include administration of growth factors, which require specific cell-surface receptors, or intervention at an intracellular level in the process of cell death by administration of antiapoptotic agents.…”
mentioning
confidence: 99%